2009
DOI: 10.3310/hta13suppl2/06
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for the treatment of relapsed or refractory stage III or IV follicular non-Hodgkin's lymphoma

Abstract: This paper presents a summary of the evidence review group report into the clinical effectiveness and cost-effectiveness of rituximab for the treatment of relapsed or refractory stage III or IV follicular non-Hodgkin's lymphoma (NHL), in accordance with the licensed indication, based upon the evidence submission from Roche Products Ltd to the National Institute for Health and Clinical Excellence (NICE) as part of the single technology appraisal (STA) process. The submitted clinical evidence included two random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…To demonstrate the flexibility/adaptability of the generic model developed in the current study, we tested two scenarios based on NICE guidelines and explored their annual economic impacts on the health care system using effect sizes reported in clinical trials [4] , [34] , which may or may not be generalizable to the patient population as a whole. In this context, the model performed well, producing results that are broadly consistent with the findings from relevant trial-based literature, although the costs for both scenarios were on the lower side [10] , [11] , [14] , [16] , [18] , [20] , [21] , [22] . In addition, although both scenarios demonstrated expected savings, wider dispersion of annual economic impact was observed in Scenario 2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To demonstrate the flexibility/adaptability of the generic model developed in the current study, we tested two scenarios based on NICE guidelines and explored their annual economic impacts on the health care system using effect sizes reported in clinical trials [4] , [34] , which may or may not be generalizable to the patient population as a whole. In this context, the model performed well, producing results that are broadly consistent with the findings from relevant trial-based literature, although the costs for both scenarios were on the lower side [10] , [11] , [14] , [16] , [18] , [20] , [21] , [22] . In addition, although both scenarios demonstrated expected savings, wider dispersion of annual economic impact was observed in Scenario 2.…”
Section: Discussionsupporting
confidence: 79%
“…In recent years, a number of economic studies have been carried out in FL treatment trials [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The majority of these have focused on comparing the cost-effectiveness of administering the monoclonal antibody rituximab at particular points along the patient pathway, either in combination with chemotherapy (immunochemotherapy) both as first-line therapy and subsequently for relapsed/refractory disease, or alone (monotherapy) either as frontline in the W&W phase or as maintenance during remission [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . However, the findings from such studies can provide only limited information to policymakers, not only because they relate to selected patients at specific points in time but also because certain groups, such as those treated palliatively and those whose disease transforms to DLBCL, are excluded [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…An effect size in the 0.4 to 0.5 range is also comparable to the outcome of trials of psychological interventions for women who have experienced domestic violence (see Appendix 7.5 in our systematic review of interventions [38]). For example, Kubany and colleagues’ two trials of CBT for women diagnosed with PTSD following intimate partner violence reported effect sizes of 0.9 [19] and 0.33 [18], respectively, for PTSD and 0.4 and 0.25, respectively, for depression outcomes.…”
Section: Methodsmentioning
confidence: 54%
“…Response duration in the treatment of FL is improving [Boland et al 2009;Cheung et al 2009;Friedberg et al 2009;Fisher et al 2005], due in part to treatment advances such as the introduction of rituximab, and the clinical benefits of rituximab maintenance [Maloney, 2008;Forstpointner et al 2006]. However, physicians continue to balance treatment decisions with the potential impact on patient HRQoL.…”
Section: Therapeutic Advances In Hematology 2 (3)mentioning
confidence: 99%